SEH AMONGRAGA (TOKOH MISTIK JAWA DALAM SERAT CENTHINI) - Fauzan Naif (UIN Sunan Kalijaga Yogyakarta, 2016)
In Javanese literature, Serat Centhini is an extraordinary work, in the term of quantities of its pages and the varieties of its content. Serat Centhini was written from January 1814 to 1823, by a team lead by Adipati Anom Amengkunagara III, Crown Prince of Surakarta Kingdom that crowned as Sunan Paku Buwana V (1820-1823) afterwards with the members such as:1) Kiai Ngabehi Ranggasutrasno, 2) Kiai Ngabehi Yasadipura II, and 3) Kiai Sastradipura. The thickness of its manuscript is around 4200 folio pages (12 editions). The content of its text is varied; include all ngelmu and kawruh that exist in Java Island. As a suluk literature, Serat Centhini also has an Islamic soul and contains Tasawwuf or Islamic Mysticism thoughts that already blend with Javanese Mysticism, for example an explanation of Javanese